Implementation of Tahfidz Al-Qur'an Activities as a Means of Fostering Student Character at Jabal Rahmah Mulia Boarding High School: Penelitian - Naura Az-Zahira; Khairun Najla Afifa; Dinda Luthfiyyah Hariadi; Farhan Abiyyu Dzaki Manik; El Hafidz Al Farid (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Education has a strategic role not only in the development of academic abilities, but also in the formation of students' character. One of the efforts made by dormitory-based schools in instilling character values is through Qur'anic tahfidz activities. This study aims to describe the implementation of tahfidz Al-Qur'an activities and its role in shaping the character of students at Jabal Rahmah Mulia Boarding High School. This research uses a qualitative approach with a descriptive design. The research subjects consisted of 21 class XII students and 2 tahfidz coaches. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis includes the stages of data reduction, data presentation, and conclusion drawn. The validity of the data is ensured through triangulation of sources and techniques. The results of the study show that tahfidz Al-Qur'an activities are carried out in a structured and sustainable manner as part of religious habituation in the boarding school environment. The methods of talaqqi, muroja'ah, and tasmi' are applied systematically with the assistance of coaches. This activity contributes to shaping the religious character of students which is reflected through the habit of reading and memorizing the Qur'an, increasing awareness of worship, and maintaining manners towards the Qur'an. In addition, tahfidz Al-Qur'an also fosters the value of discipline, responsibility, and istiqamah which can be seen from compliance with the activity schedule, seriousness in achieving memorization targets, and consistency in maintaining memorization. Thus, tahfidz Al-Qur'an activities play an important role as a means of fostering students' character in the boarding school environment.